THE ROLE OF EMPATHY IN CREATING A FAVORABLE PSYCHOLOGICAL CLIMATE IN A PRESCHOOL EDUCATIONAL ORGANIZATION - Bekmanova, Jamila Abdulayevna (SCIENCE and SOCIETY, 2026)
This article examines the role of empathy as a key psychological mechanism in creating a favorable psychological climate in a preschool educational institution (PEI). Theoretical approaches to defining the concepts of “empathy” and “psychological climate” are analyzed, and the structural components of a teacher’s empathy and their influence on interpersonal relationships within a children’s group are explored. Practical recommendations are presented for developingempathic abilities among preschool teachers and specialists. Theim portance of empathic interaction in the “teacher–child” and “teacher–parent” relationships for the psychological well-being of all participantsin the educational process is substantiated.